Intervention of job stress and employee morale on organizational culture and employees’ job efficiency. - Kiran Kumar Thoti (2016)
Information and communication technology (ICT) skills have becoming the basic requirements for individuals to compete in the global market. Technology has incredible power to improve people’s lives, to foster economic growth, and to create opportunities for individuals, companies, and nations around the globe. Over the past 13 years, the transformation of information and communication technologies has been well documented. The transformation of ICT has resulted in the emergence of new challenges to employees and on employment matters. Issues such as brain drain, workmen compensation, treatment of foreign workers, terms of employment and organizational safety and health and new ways of working methods have taken on new dimensions and may necessitate changes to the existing regulations. Hence, these challenges require new work culture and create increasing job stress among employees which visibly affects the moral and efficiency of the employees. The purpose of this study thus, is to examine the relationship between the organizational culture and job efficiency with the intervening variables of job stress and employee morale among employees in the ICT industries in Malaysia. This study enhances the organizational behavior discipline in particular the stress literature. The examination of organizational culture in influencing employee stress and morale would significantly impact the organizational behavior studies. The Malaysian information technology companies are relatively young and are rapidly heading toward reaching the number one in the global ICT industry. The respondents studied were employees who are working in the information technology companies in Malaysia. The sample size was drawn from the directory of the information technology companies in Malaysia and also from the list of companies involved. A total of 600 questionnaires were sent and 237 or 39.5 percent responded. The questions were measured on a five point Likert-scale ranges from Strongly Disagreed (1) to Strongly Agreed (5). The software used for data analysis for this research was SPSS 20.0 and AMOS 20.0.The findings discovered that organizational culture has positive influence on job efficiency. In addition, the culture variable has significant effect also on job stress and employee morale. The other important findings is that both job stress and employee morale has significant intervening effects on the relationship between organizational culture and job efficiency among the respondents studied. The results have demonstrated that organizational culture is an important contributing factor for enhancing cultural practices in an organization. In addition, the recognition for cultural values and employee value propositions as significant factors in influencing job stress and employees’ morale is deemed to be important for ICT companies to address and manage employee stress and well-being in the long run.